The Kite runner - Khalid, Hossaini (London Bloomsburry, 2003)
"The Kite Runner," written by Khaled Hosseini, is a poignant story about friendship, betrayal, and redemption set against the backdrop of a changing Afghanistan. The narrative follows Amir, a young boy from a wealthy family, and his close friend Hassan, the son of his father's servant
Keywords: English- text